Bagliettoa perseae (Verrucariaceae), a new species from historic stone surfaces in Persepolis, a UNESCO World Heritage Site in Iran - Sohrabi, Mohammad; Esmaeillou, Mahsa; Gueidan, Cécile; Bungartz, Frank; Pérez-Ortega, Sergio (Phytotaxa, 2025)
Bagliettoa perseae sp. nov., a novel lichen species, is described from Persepolis, a UNESCO World Heritage Site in Iran. This species is characterized by its endolithic growth within calcareous substrates, a magenta-pigmented involucrellum, and large ascospores. Phylogenetic analyses, utilizing maximum likelihood and Bayesian inference based on nuclear ribosomal ITS and mitochondrial small subunit (mtSSU) regions, unequivocally place the new taxon within the genus Bagliettoa (Verrucariaceae). Bagliettoa perseae forms a well-supported clade with B. marmorea and B. rubrocincta, although phylogenetic resolution within this clade remains ambiguous. Morphological comparisons with closely related Bagliettoa species are provided. Furthermore, the taxonomic identity of Verrucaria buschirensis, described 126 years ago from southern Iran, was reassessed. Based on congruent morphological and molecular data, V. buschirensis is herein proposed as a new synonym of Bagliettoa calciseda.